Writing against “Mask Culture”: Orientalism and COVID-19 Responses in the West - Zhang, Mingyuan (Anthropologica, 2021)
Since the first coronavirus outbreak hit China in January 2020, how different countries respond to the crisis has sparked interesting discussions regarding to their respective history, political systems and culture. In the West, many people attribute the acceptance of universal mask-wearing among Asian populations to a so-called ’mask culture.’ This paper argues that ’mask culture’ emerges during the pandemic as an Orientalist concept in Western public discourses to define the East and to freeze differences between ‘self’ and ‘other.’ Orientalism in its everyday manifestation has not only contributed to the initial underestimation of the pandemic in the West; but has also provided a culturalist foundation for essentialist representations of Asian cultures. Self-other binary has greatly shaped Western responses to and narratives of the pandemic in two prominent ways: first, mask-wearing has been considered as an ‘Asian’ practice associated with other Asian cultural stereotypes such as submissiveness to state power; and second, the threat of the coronavirus was initially viewed as minimal because outbreaks in Asia were far and distanced, and thereafter, the suffering of the Other was not considered urgent in the West.